Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.4 Derivatives of Logarithmic Functions - 6.4 Exercises - Page 437: 52


$y'=(sinx)^{lnx}[lnx cotx+\frac{1}{x}ln(sinx)]$

Work Step by Step

Given: $y =(sinx)^{lnx}$ Taking logarithmic on both sides of the function $y =(sinx)^{lnx}$ $lny=lnx ln(sinx)$ Take implicit differentiation with respect to $x$. Apply product rule of differentiation. $\frac{d}{dx}(lny)=\frac{d}{dx}[lnx ln(sinx)]$ $\frac{1}{y}\frac{d}{dx}(y)=lnx\frac{d}{dx}[ln(sinx)]+ln(sinx)\frac{d}{dx}(lnx)$ $\frac{d}{dx}(y)=y[lnx\times\frac{1}{sinx}\frac{d}{dx}(sinx)+ln(sinx)\frac{d}{dx}(lnx)]$ $\frac{d}{dx}(y)=y[lnx\times\frac{1}{sinx}(cosx)+ln(sinx).\frac{1}{x}]$ Hence, $y'=(sinx)^{lnx}[lnx cotx+\frac{1}{x}ln(sinx)]$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.